Adaptation of Handbook for Development of Intercultural Competence: the Experiences - Navaitienė, Julita; Račelytė, Daiva; Rimkevičienė, Violeta (Pedagogika, 2015)
The present reflection article discloses the experiences gained during the adaptation of the material for intercultural competence development. The resource book Building Intercultural Competences: A Handbook for professionals in education, social work and health care was selected and its material was adapted to educational context of VET students and teachers. The framework of adaptation of the Handbook is presented in the article. The study was done to investigate the VET students’ and teachers’ needs for intercultural competence development.